Paradoxical exacerbation of chronic plaque psoriasis by sorafenib. (15th December 2015) - Yiu, Z. Z. N.; Ali, F. R.; Griffiths, C. E. M.
Summary: Vascular endothelial growth factor (VEGF) antagonists have been investigated as a potential treatment for psoriasis, but there have been reports of VEGF antagonists triggering and/or exacerbating pre‐existing psoriasis. We present the case of a 61‐year old‐man with exacerbation of pre‐existing psoriasis after treatment with sorafenib, a small molecule inhibitor of the tyrosine kinase domain of the VEGF receptor, and we review the literature for other published cases of sorafenib‐induced or sorafenib‐exacerbated psoriasis. Clinicians, including both dermatologists and oncologists, should be aware of this potential side‐effect of sorafenib in addition to the other cutaneous side effects reported for this drug.